Nová metoda měření krevního tlaku v ordinaci lékaře - automatický klinický TK - Šuláková, Terezie; Burešová, Miroslava; Juráková, Kristýna; Řepišťák, Michal; Pavlíček, Jan; Seeman, Tomáš (Pediatrie pro praxi, 2023)
Accurate blood pressure (BP) measurement and its correct interpretation are essential factors influencing proper diagnosis and hypertension therapy. There are 5 methods of BP measurement. The office/casual/clinic blood pressure measurement has a central role as the most used method. This measurement is significantly influenced by its users and also by patient's response. Therefore, most of hypertension guidelines in adults but also in pediatrics have recommended out-of-office BP methods, i.e. home blood pressure measurement or ambulatory blood pressure monitoring. Automated office blood pressure measurement (AOBP) with the patient alone in a room is new method of BP measurement recommended for BP measurement in adult population. The aim of the paper is AOBP overview about its use in adults and children age.
Keywords: Hypertension; hypertenze; krevní tlak; měření krevního tlaku; lidé; Blood Pressure; dítě; ambulantní monitorování krevního tlaku; Child; Humans; Blood Pressure Determination; automatické klinické měření krevního tlaku; Blood Pressure Monitoring, Ambulatory